Symptomatic cysts of the telencephalic choroid plexus - Neblett, Charles R. (1971)
Symptomatic cysts of the telencephalic choroid plexus are rare. This is a paediatric problem, with the oldest patient being 10 years old. Pertinent cases from the literature are reviewed. The case of a 9 year old girl with suboccipital headaches made more severe by lying on her right side or on her abdomen is discussed. Physical examination was within normal limits except for evidence of early papilloedema. The cerebrospinal fluid pressure was normal, and the protein was not elevated (32 mg/100 ml.). The brain scan showed a left frontoparietal mass near the midline, and the electroencephalogram was abnormal. The pneumoencephalogram demonstrated a mobile, pedunculated mass in the left trigone which approached the foramen of Monro when the patient assumed the head-erect position. A transcallosal approach was used and the cyst was easily removed. Postoperatively the patient has done well and is currently asymptomatic and without headaches. The significance of the presenting symptoms, the cerebrospinal fluid and brain scan findings, as well as the surgical approach, are discussed.